Can high-intensity functional suspension training over eight weeks improve resting blood pressure and quality of life in young adults?: a randomized controlled trial - Engel, Florian; Rappelt, Ludwig; Held, Steffen; Donath, Lars (International journal of environmental research and public health, 2019)
The present study examined the effects of a functional high-intensity suspension training (FunctionalHIIT) on resting blood pressure, psychological well-being as well as on upper body and core strength and cardiorespiratory fitness in moderately trained participants. Twenty healthy, moderately trained adults (10 males and 10 females; age: 36.2 +/- 11.1 years, BMI: 23.9 +/- 3.7) were randomly assigned to a FunctionalHIIT training group or passive control group (CON). FunctionalHIIT performed 16 sessions (2x week for eight weeks, 30 min per session), whereas CON maintained their habitual lifestyle using a physical activity log. Before and after FunctionalHIIT intervention, resting blood pressure and quality of life (short version of the WHO Quality of Life questionnaire (WHOQOL-BREF)) were assessed. Furthermore, maximum-repetition (leg press, chest press, pulldown, back extension) and trunk muscle strength (Bourban test) as well as cardiorespiratory fitness (Vameval test), were measured before and after the intervention. Both systolic and diastolic blood pressure and WHOQOL-BREF did not change significantly but both showed moderate training-induced effects (0.62 > standardized mean difference (SMD) > 0.82). Significant improvements in the FunctionalHIIT group were evident on leg press (p > 0.01), chest press (p > 0.05), and left side Bourban test (p > 0.05). Cardiorespiratory fitness did not reveal any time effects or time x group interactions. The present study revealed that eight weeks of FunctionalHIIT represents a potent stimulus to improve health-related parameters in young adults, whereas FunctionalHIIT was not sufficient to improve cardiorespiratory fitness.